Analysis of a switching angle calculation by ANN for nine level inverter apply into experimental case study with elimination of lower and higher order harmonics - Mohammed Rasheed; Rosli Omar; Marizan Sulaiman; Wahidah Abd Halim; Moataz M.A. Alakkad (Institute of Advanced Engineering and Science, 2020)
This paper confers an investigation of a selective harmonic elimination (SHE) technique has gained wide acceptance for many AC drive applications, due to a higher DC bus voltage utilization (higher output voltage compared with the sinusoidal pulse width modulation (SPWM), lower harmonic distortions and easy digital realization.” In recent years, the SHE technique was extensively adopted in multilevel inverters since it offers greater numbers of switching for obtaining further improvements of AC drive performances. “Nevertheless, the use of SHE-associated multilevel inverters will optimize the switching angles based on artificial neural networks (ANN) compared with particle swarm optimization (PSO) to reduce the total harmonic distortion (THD) of the modified CHB-MLI output voltage within permissible limits. The main objectives of this paper are the design and testing of the CHB-MLI modified topology laboratory for a nine-level single-phase prototype.” Also demonstrated were the experimental effects of using Digital Signal Processing (DSP) TMS320F2812 into a prototype. The controls were applied to the modified multilevel inverter, based on ANN and PSO. The proposed controller was then coded onto a board of DSP TMS320F2812. Compared with the PSO method, the inverter gives fewer THD using ANN scheme.